Impact of covid 19 pandemic on presentation,treatment and outcome of paediatric surgical emergencies - Ali, Sajjad; khan, Muhammad Asim; Rehman, Inayat ur; Uzair, Muhammad (Journal of Ayub Medical College Abbottabad, 2021)
Background: During the current pandemic it was observed that factors such as lockdown, campaign to discourage unnecessary visits to hospitals, inadequate clinical evaluation and investigations culminated in serious complications of common paediatric surgical conditions. This observation led to the basis of the idea to statistically and objectively evaluate the impact of the current pandemic on paediatric surgical emergencies. Methods: Data of paediatric surgical emergencies during March-May 2019 and March-May 2020 was collected from database of the paediatric surgical department of Khyber Teaching Hospital Peshawar and two groups were constituted, i.e., Pre COVID and COVID groups respectively. These two groups were compared for the number of emergency admissions, the number of emergency surgeries, complications at the time of presentation and surgical treatment given. Data were analysed in SPSS version-22 and p-value after Yates correction was generated were necessary to see if the difference was statistically significant (p<0.05). Results: There were 47.8% fewer emergency admissions and a 77.45% reduction in the number of emergency surgeries done in COVID time as compared to the Pre COVID time. Similarly, the number of perforated appendicitis and complicated intestinal obstruction was significantly higher than expected in COVID group. Same was the difference in the number of patients requiring extensive surgery between the groups. Conclusion: Delay in presentation, complications and requirement for extensive surgical procedure are the indirect impacts of the current pandemic on emergency surgical conditions of children. Keywords: COVID 19; Pandemic; Paediatric; Emergency